2013
DOI: 10.1177/1754337113493847
|View full text |Cite
|
Sign up to set email alerts
|

Kayak blade–hull interactions: A body force approach for self-propelled simulations

Abstract: A sprint kayak experiences an unsteady flow regime due to the local influence of the paddle. However, kayak designs are usually optimised for steady-state, naked hull resistance. To determine whether unsteady paddle effects need to be included in kayak design, the hydrodynamic interactions between a kayak paddle and a hull are assessed using computational fluid dynamics. A body force model of a drag-based paddle stroke is developed using a blade element approach and validated against experimental data. This al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This discrepancy could be due to a range of factors such as uncertainty regarding the arm orientation, variable chord length down the arm, different lift and drag coefficients associated with the tested athlete's arm or unsteady effects not captured in the quasi-steady approach adopted. Indeed, the unsteady forces measured on a rotating kayak paddle were found to be significantly higher than a similar quasi-steady approximation presented by Banks et al 26 Therefore, to include the athlete-specific unsteady effects into the body force model, a factor of two was applied to the forces generated by the arm model, so as to replicate the mean tow force (R -T) measured during the experiment. This should ensure that the correct magnitude of thrust is applied to the fluid around the swimmer, despite some uncertainty regarding the exact distribution in time.…”
Section: Validation Of Passive Resistance Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…This discrepancy could be due to a range of factors such as uncertainty regarding the arm orientation, variable chord length down the arm, different lift and drag coefficients associated with the tested athlete's arm or unsteady effects not captured in the quasi-steady approach adopted. Indeed, the unsteady forces measured on a rotating kayak paddle were found to be significantly higher than a similar quasi-steady approximation presented by Banks et al 26 Therefore, to include the athlete-specific unsteady effects into the body force model, a factor of two was applied to the forces generated by the arm model, so as to replicate the mean tow force (R -T) measured during the experiment. This should ensure that the correct magnitude of thrust is applied to the fluid around the swimmer, despite some uncertainty regarding the exact distribution in time.…”
Section: Validation Of Passive Resistance Methodsmentioning
confidence: 95%
“…Body force models have previously been used to model propeller-hull interactions, 23,24 tidal turbine arrays 25 and the impact a kayak paddle has on the propelled resistance of a sprint kayak. 26 This approach allows the effect of the free surface and unsteady arm motion to be simulated while ignoring the detailed local effects of the arm's boundary layer. If the focus is on investigating the effect of the arm-induced flow velocities, instead of the accompanying torso motion, a rigid mesh can be used around a static swimmer geometry for the CFD simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic aspects of the propulsion have been investigated extensively; the hydrodynamic drag or its components was analyzed both computationally and experimentally [1][2][3][4][5][6], even under uniform displacement conditions. The paddle [7] or stroke [8] hydrodynamics were also analyzed; correlations between the stroke frequency and hull speed [9][10][11], the stroke force versus time functional relation [9,12] or the hull-stroke interaction [13,14] were found. There are also studies on the forces applied to the paddle blade and the power, accelerations and velocities that it produce in the hulls [9,12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CFD-based shape optimisation studies can be found in other references. [15][16][17][18] The major aim of this work is to employ the genetic algorithms and response surface based model (RSM) to present a technique for the surfboard fin shape optimisation. The study combines CFD simulations using the FLUENT Ò code with genetic algorithms to obtain an optimal fin shape, which presents maximum lift-to-drag ratio (L/D ratio).…”
Section: Introductionmentioning
confidence: 99%